A study of the place of the eucharist in ecumenical discussion - Reimers, D G (Rhodes University, Faculty of Divinity, Department of Divinity, 1964)
Christian disunity, as has been shown by Rouse and Neill, has been a major problem in the Church from the time of its inception. In Apostolic times Paul had to face serious dissension at Corinth and elsewhere. The great councils of the 4th and 5th centuries were convened to settle doctrinal disputes. The schism between Eastern and Western Christianity, which finally became permanent at about the end of the 12th century, was the result of thoroughgoing doctrinal as well as cultural differences. At the Reformation, Christianity was again drastically divided and between the 16th and 19th centuries,divisions were greatly multiplied. Chap. 1, p. 1.
Keywords: Ecumenical movement; Lord's Supper